Relationship between mentoring program and mentees' study performance - Azman Ismail; Najihah Omar; Khaidzir Ismail (Pusat Perkembangan Pelajar ,UKM, 2014)
This study aimed at investigating the relationship between mentoring program and mentees' study performance. A survey method was employed to gather self-report questionnaires from undergraduate business students at a research university in Malaysia. The results of SmartPLS path model revealed two important findings: firstly, communication positively and significantly correlated with study performance. Secondly, support positively and significantly correlated with study performance. The result confirms that mentoring program does act as an important predictor of mentees ' study performance in the studied organization. In addition, discussion, implications and conclusion are elaborated.